New Concepts of Human Interactions and Collaborative Robot-Manipulators in the Concepts of Industry 5.0 - Vladyslav Yevsieiev; Dmytro Gurin (Collection of scientific papers «SCIENTIA», 2024)
Collaborative robotics is a part of robotics that studies, researches and practices the application of CPR in interaction (collaboration) with a person during the performance of various technological operations and tasks. Collaborative robots (cobots) are robots designed for direct H–R (human-robot) interaction in a shared workspace or where humans and robots are in direct contact. Collaborative robot programs differ from traditional PR programs, in which robots are isolated from contact with humans. As defined by the International Organization for Standardization, a cobot is a robot that can be used in collaborative operations where robots and humans work simultaneously within a defined workspace for manufacturing operations (this does not include robot-to-robot systems or co located humans and robots working at different times). Collaboration (in the context of industrial robotics) is the process of joint performance of an operation, action or work by a person and a robot to achieve a set goal.
Keywords: collaborative robotics; Industry 5.0; robots designed for direct H–R